Individual Adaptability to Work: Scale Validation on the Romanian Population - Botezat, Elena Aurelia; Crisan, Daniela; Fotea, Silvia Liana; Fotea, Ioan Stefan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
This study aimed to validate the I-ADAPT scale to assess the individual adaptability to work within the Romanian population. Both a pilot study and a main study were conducted on a total sample of 966 Romanians. Following the application of standard scale validation procedures, the results of our study indicated that the I-ADAPT measure of work adaptability has good psychometric properties on the Romanian population. Our findings provide evidence that I-ADAPT continues to explain the unique variance in adaptability to work even if work patterns in the Covid-19 pandemic context moved more and more from a traditional to a virtual work environment. ROa I-ADAPT measure has excellent properties concerning convergent, discriminant, and criterion-related validity. One main finding was that the “Physical” dimension of adaptability to work had no empirical support in the Romanian population. Moreover, our results indicate that the “interpersonal adaptability” and the “cultural adaptability” dimensions cannot be empirically separated in the Romanian population. To our knowledge, this is the first validated instrument that can be used to assess the individual adaptability of Romanians in the context of work. Our study is relevant for decision-makers in Romania and such actors in other EU-member countries where Romanians represent the largest group of working-age EU citizens.